ANALISIS USAHATANI PADI SAWAH DI KABUPATEN MAGETAN PROVINSI JAWA TIMUR - Viona Ade Zarahma; Sri Marwanti; Ernoiz Antriyandarti (Syarif Hidayatullah State Islamic University Jakarta, 2019)
This study aims to determine the analysis of rice farming in Magetan Regency, East Java Province. The implementation technique used in the research is survey technique. The sampling area method was carried out using a purposive method, which is to determine the location of sampling area taken purposely based on certain considerations in accordance with the research objectives. The result come with farming costs with an average land area of 0.90 hectares are IDR. 11.312.100,00, with an average variable cost of IDR. 5.317.000,00 and the average fixed costs of IDR. 5.995.100,00. The average farm income is IDR. 24.118.000,00. The average farm income is IDR 12.805.900,00. BEP and R / C Ratio analysis showed that farming was carried out favorably for farmers in Gunungan Village, Kartoharjo District, Magetan Regency, East Java Province. With the R / C ratio of 2.13.